Potensi Pengembangan Investasi Berbasis Ekonomi Kreatif Pada Era New Normal di Kota Surakarta - Destina Paningrum (Universitas Sahid Surakarta, 2021)
The creative economy is a concept that is always echoed by intensifying information and creativity that relies on ideas and knowledge from human resources as the main production factor. Creative Economy actors are divided according to sub-sectors, including: Architects, Interior Design, Visual Communication Design, Apps and Games, Product Design, Fashion, Video Film and Animation, Photography, Crafts, Culinary, Publishing, Fisheries, Performing Arts, Music, Arts From TV and Radio. The Covid-19 outbreak that has hit Indonesia since early March 2020 has had a significant impact on various sectors and one of these sectors is the economic sector, namely the creative industry. The government has begun to discuss a new normal (new normal) as an effort to restore the economy. The data analysis model used in this research is descriptive analysis with qualitative data. The results of this study include: (1) Through performing arts, product design, fashion, and culinary, it is hoped that it will be able to increase creative industry players who have competitiveness at both regional and national levels, to international levels (2) Assistance from local governments such as MSME loan restructuring facilities, labor-intensive programs, as well as providing relief from regional levy taxes for MSMEs to guide the creative industry to be more advanced amidst the uncertainty of the national economy in the new normal era. (3) Productive areas, such as Jebres District, can be used as a model forcreative industries for local people. other sub-districts in the city of Surakarta, even pilots in cities outside Surakarta.